Pemerintahan Tradisional di Dataran Tinggi Karo Masa Pemerintahan Kolonial Belanda - Irianna, Irianna (Analisis Sejarah, 2024)
This article discusses the influence of the Sultanate of Aceh since 1868 on the traditional Karo leaders who ruled in the five sebayak or kingdoms of Sebayak Lingga, Suka, Barus Jahe, Sarinembah and Kuta Buluh. Aceh's influence extended to only four of the five kingdoms, with Kuta Buluh remaining independent. Aceh's influence was less profound among traditional Karo leaders and almost non-existent among the general population, as Acehnese Islamic traditions and religion were not adopted at that time. Dutch rule began to influence traditional Karo leaders in 1905, but it wasn't until 1908 that it became region-wide. Dutch influence was very strong, both on the leaders and the Karo people. The Dutch completely controlled the leaders in the Karo plains, who in turn applied their leadership to their subordinates, the Raja Urung who ruled the urung and the Penghulu who ruled the village. The Dutch also regulated the government system, changing the name of kesebayakan into Landschappen, and restructuring the number of urung. This research uses the historical method with an analytical descriptive approach to discuss the government system and social life during the influence of the Sultanate of Aceh and the Dutch in the Karo highlands.